Marriage Dispensation Following Amendments to the Marriage Law: A Study on the Legal Awareness of the Jember Regency Community - Suryanti, Rina; Anisah, Inayatul; Martoyo, Martoyo (Jurnal Ilmu Hukum Kyadiren, 2026)
Five years after the amendment of Law No. 16 of 2019, applications for marriage dispensations have risen sharply, particularly in Jember Regency, which recorded the highest rate in East Java. This article examines whether this phenomenon reflects an increase in legal awareness or merely administrative compliance with the ongoing practice of child marriage. Using a juridical-sociological approach, this study combines normative analysis of legal regulations and concepts with empirical data obtained through observation, interviews, and documentation. The findings reveal that although Supreme Court Regulation (PERMA) No. 5 of 2019 provides clear guidelines for judges, Pandalungan cultural influences and socioeconomic factors continue to sustain early marriage practices. The surge in cases demonstrates a form of instrumental legal awareness—people understand the law but utilize it to maintain traditional norms. This research recommends strengthening evidentiary standards, implementing mandatory psychosocial and medical assessments, and promoting community-based prevention strategies.